6th grade students' narratives about remote learning - Junqueira, Carmita de Souza Oliveira (2022)
This study deals with the experiences of a Portuguese language teacher in the context of Emergency Remote Teaching (ERE), in the second half of 2020, in the 6th grade class A. The purpose of this article is to narrate the experiences, learnings and challenges of students regarding the relationship between face-to-face and online classes, due to the Covid-19 pandemic. The data produced and analyzed are made up of narratives from 12 students, written at home, in Portuguese language classes on September 14, 2020, and sent to the WhatsApp Group. The shared narratives point out that the ERE as an educational alternative in the face of the pandemic, highlighted problems related to access to technological devices (devices and internet). On the other hand, the stories of experiences told by the students express greater involvement of families in the development of online activities, thus strengthening the bond between school and family.